Comparative analysis of the core inflation for Russia - A. K. Sapova (Статистика и экономика, 2016)
Consumer price index is a measure of inflation and it consists of two parts: persistent component (trend inflation) and short-term shocks. Inflation targeting requires index of core inflation, that independent from shortterm shocks and demonstrates the changes of the trend inflation. Reserve Banks pay attention on the changes in the trend inflation, when they take decisions about monetary policy, because it’s more informative than consumer price index for estimation of medium-term inflation risks. The objective of this article is detecting the index of core inflation that could be appropriate for monetary policy. There are some different measures of core inflation based on practice of Reserve Banks from different countries and economic articles. The comparative analysis presented in this article is based on several types of tests. The result of the research is that core consumer price index that is used today has got both advantages and weaknesses. Moreover, there is index of core inflation based on new methodology that is better than core consumer price index of Federal Sate Statistics Service. It is concluded that the Central Bank should focus precisely on this indicator when it takes decisions about monetary policy.